2010
DOI: 10.1016/j.jacc.2010.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reverse Remodeling With Cardiac Resynchronization Therapy

Abstract: CRT patients with uneventful survival show a significant decrease in the LVSVi at 6 months and generally maintain this response in the long term. Those with adverse outcomes are characterized by left ventricular dilation despite CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 30 publications
3
62
0
5
Order By: Relevance
“…Of the 7 identified baseline clinical and echocardiographic covariates that made up the response score in the present study, 4 clinical variables were also previously reported to predict reverse remodeling in patients with more advanced HF symptoms: a nonischemic origin of cardiomyopathy, 15,21,22 female sex, 22,23 QRS width, 2,22,24 and the presence of left bundle-branch block on the baseline ECG. 25,26 In contrast, prior studies did not identify baseline cardiac volumes and a history of HF hospitalization as independent predictors of LV reverse remodeling in patients with advanced HF symptoms.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Of the 7 identified baseline clinical and echocardiographic covariates that made up the response score in the present study, 4 clinical variables were also previously reported to predict reverse remodeling in patients with more advanced HF symptoms: a nonischemic origin of cardiomyopathy, 15,21,22 female sex, 22,23 QRS width, 2,22,24 and the presence of left bundle-branch block on the baseline ECG. 25,26 In contrast, prior studies did not identify baseline cardiac volumes and a history of HF hospitalization as independent predictors of LV reverse remodeling in patients with advanced HF symptoms.…”
Section: Discussionmentioning
confidence: 71%
“…25,26 In contrast, prior studies did not identify baseline cardiac volumes and a history of HF hospitalization as independent predictors of LV reverse remodeling in patients with advanced HF symptoms. 22 Thus, it is possible that the relationships between the last 3 predictors of reverse remodeling in MADIT-CRT are specific to the study population, or our sample from it, that was made up of patients with less advanced HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the models with the break point set up at the 3rd, 90th, 180th, and 360th day of CRT. 15,23 In a second step, we assessed the timed-dependent correlation between changes in MR and the amount of reverse remodeling during CRT. For this purpose, we again used a linear mixed-effects model approach to correlate VC change from baseline with percentage LVESVi change from baseline, with the time covariate set to 0 if the data were assessed during the first 7 days and to 1 if otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…15 Patients with a major event during these first 3 months (early death or urgent trans-plantation) were excluded. Baseline and every subsequent echocardiogram obtained at our institution during the follow-up of the patient after initiation CRT were systematically reviewed and measured by 2 experienced readers (D.V.…”
Section: Study Population and Study Designmentioning
confidence: 99%
“…20,21 Reverse remodeling with CRT occurs primarily within the first 6 months after implantation and provides strong prognostic benefit in patients with traditional indications. 22 Therefore, the demonstration of reverse remodeling in both MADIT-CRT and REVERSE provides a very strong argument for CRT based on the ability of this intervention to directly improve the biological changes resulting from the pathophysiology of HF. However, reverse remodeling did not occur in all patients despite the intended purpose of restoring synchrony with CRT.…”
Section: Do the Hf Events In The Primary End Point That Were Reduced mentioning
confidence: 99%